Digitization and digital archiving. A practical guide for librarians - Leggett, Elizabeth R. (Practical guides for librarians., 2021)
To help new archivists and genealogists with what can be a daunting process, 'Digitization and Digital Archiving: A Practical Guide for Librarians' answers common questions, including:001. What should be stored?02. Where and how should it be stored?03. How exactly is information stored in a computer?04. How does copyright law affect archiving?05. How can metadata be used to improve collection access?00This revised second edition has been updated to address new trends and the latest innovations in technology, including:001. A brand-new chapter addressing different common types of born-digital materials which a librarian may need to archive, such as databases or websites02. Information about identifying and gathering data from floppy disks, an increasingly important task as this technology ages and its data becomes at greater risk of loss03. Fully updated chapters to address the latest changes in file storage and formats, including more information on the storage of audio and video media04. Interesting information about the origins of different common technologies to help the reader better understand the past, present, and future of computer technology00This is a comprehensive guide to the process of digital storage and archiving. Assuming only basic computer knowledge, this guide walks the reader through everything he or she needs to know to start or maintain a digital archiving project. Any librarian interested in how digital information is stored can benefit from this guide.